Growth and physiological responses of Quercus brantii seedlings inoculated with Biscogniauxia mediterranea and Obolarina persica under drought stress. Issue 5 (19th May 2017) - Ghanbary, E.; Tabari Kouchaksaraei, M.; Mirabolfathy, M.; Modarres Sanavi, S. A. M.; Rahaie, M.
Summary: Charcoal canker of oak is a common disease in the western regions of Iran, which has widely spread due to climate change and increasing drought in recent years. Biscogniauxia mediterranea and Obolarina persica are known as two agents of oak charcoal canker in Zagros forests causing the dieback of oak trees. The effects of charcoal disease agent pathogens on the growth and physiological response of two‐year‐old seedlings of Quercus brantii were evaluated under drought stress in greenhouse over a period of nine months. Survival was 21.7% lower in seedlings inoculated with B. mediterranea subjected to drought stress compared with control treatment. The length of lesions on stems was 68% more under charcoal pathogens in drought stressed compared with the length of lesions caused by charcoal pathogens only. On the other hand, stem lesion length caused by B. mediterranea was 25% greater than those caused by O. persica . Some morphophysiological characteristics were affected by charcoal pathogens alone and/or in combination with drought. Diameter, height and biomass decreased the most in seedlings inoculated with charcoal pathogens under drought stress. Pathogenic agents alone and in combination with drought stress reduced photosynthetic rates, stomatal conductance, transpiration, the maximum Rubisco activity ( V cmax ), maximum photochemical efficiency of photosystem II ( F v / F m ) and xylem water potential. In general, drought increased the aggressiveness of fungus and intensification of their destructive effects in Quercus brantii . Moreover, there was no significant difference between the effect of B. mediterranea and O. persica on the morphophysiological parameters studied.